Clinical use of ultrasonic cw doppler technique in stomatology - MAGNUS, S.; PARDEMANN, G.; THIERFELDER, Ch.; VOGEL, S. (Archives of Acoustics, 1979)
All methods used in stomatological practice for assessment of blood supply to the pulp require sensitivity testing. This, however, is not a reliable diagnostic method. Blood movement in the pulp can be detected directly by means of CW Doppler ultrasound. This technique, consequently, is an objective method which seems to be suitable for the above purpose, The author's approach to the problem has been theoretical, with the view to examining the suitability of the method and to establishing technical parameters of a stomatological Doppler device. Preliminary results so far obtained from the use of the ultrasonic Doppler technique in testing blood supply to the tooth are presented in this paper. Both advantages and disadvantages of the method are discussed.